2017
DOI: 10.1093/mnras/stx2284
|View full text |Cite
|
Sign up to set email alerts
|

Interplanetary Scintillation with the Murchison Widefield Array I: a sub-arcsecond survey over 900 deg2 at 79 and 158 MHz

Abstract: We present the first dedicated observations of Interplanetary Scintillation (IPS) with the Murchison Widefield Array (MWA). We have developed a synthesis imaging technique, tailored to the properties of modern "large-N" low-frequency radio telescopes. This allows us to image the variability on IPS timescales across 900 square degrees simultaneously. We show that for our observations, a sampling rate of just 2 Hz is sufficient to resolve the IPS signature of most sources. We develop tests to ensure that IPS var… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 56 publications
0
59
0
Order By: Relevance
“…The Phase I MWA was motivated by a vast array of science goals spanning initial observations of the EoR power spectrum, Galactic and Extragalactic continuum and polarimetry, solar and ionospheric science, and detection of transient sources (Bowman et al 2013). In addition to covering the initial science goals, the Phase I MWA also produced a number of unforeseen results including the first detection of plasma tubes in the ionosphere (Loi et al 2015a(Loi et al , 2015b, the potential to utilise the MWA for space debris detection and tracking (Tingay et al 2013b;Zhang et al 2018), tentative detections of new molecules (Tremblay et al 2017), and use of interplanetary scintillation to identify and measure subarcsecond compact components in low-resolution, low-frequency radio surveys without the need for long baseline interferometry or ionospheric calibration (Kaplan et al 2015a;Morgan et al 2018;Chhetri et al 2018). The wide field of view and pointing agility of the MWA have also proven invaluable for both targeted and archival searches (from serendipitous observations) for radio emission associated with astronomical events such as gammaray bursts (Kaplan et al 2015b), neutrino detections (Croft et al 2016), gravitational wave events (Abbott et al 2016(Abbott et al , 2017, and interstellar visitors (Tingay et al 2018).…”
Section: Scientific Motivation For the Upgradementioning
confidence: 99%
“…The Phase I MWA was motivated by a vast array of science goals spanning initial observations of the EoR power spectrum, Galactic and Extragalactic continuum and polarimetry, solar and ionospheric science, and detection of transient sources (Bowman et al 2013). In addition to covering the initial science goals, the Phase I MWA also produced a number of unforeseen results including the first detection of plasma tubes in the ionosphere (Loi et al 2015a(Loi et al , 2015b, the potential to utilise the MWA for space debris detection and tracking (Tingay et al 2013b;Zhang et al 2018), tentative detections of new molecules (Tremblay et al 2017), and use of interplanetary scintillation to identify and measure subarcsecond compact components in low-resolution, low-frequency radio surveys without the need for long baseline interferometry or ionospheric calibration (Kaplan et al 2015a;Morgan et al 2018;Chhetri et al 2018). The wide field of view and pointing agility of the MWA have also proven invaluable for both targeted and archival searches (from serendipitous observations) for radio emission associated with astronomical events such as gammaray bursts (Kaplan et al 2015b), neutrino detections (Croft et al 2016), gravitational wave events (Abbott et al 2016(Abbott et al , 2017, and interstellar visitors (Tingay et al 2018).…”
Section: Scientific Motivation For the Upgradementioning
confidence: 99%
“…A detection of IPS with the MWA was first made serendipitously in night-time astrophysical data by Kaplan et al (2015a). Following this, a pilot study was made using observations designed for the purpose, at solar elongations most suitable for detecting IPS (Morgan et al 2018). This pilot study demonstrated that the MWA has a unique capability for detecting IPS of several hundred sources simultaneously in a single 5-min observation.…”
Section: Interplanetary Scintillationmentioning
confidence: 99%
“…Solar observations require extremely high dynamic range, which has led to new imaging and calibration techniques (Oberoi et al 2017;Mohan & Oberoi 2017). The SHI group has characterised weak nonthermal solar emission (Suresh et al 2017;Sharma et al 2018) and detected IPS due to solar wind both serendipitously (Kaplan et al 2015a) and with directed observations (Morgan et al 2018). One of the most exciting discoveries from the MWA has been the first direct detection of plasma ducts aligned with the Earth's magnetic field in the ionosphere (Loi et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…We determined the magnitude of the interplanetary scintillation (IPS) exhibited by our sources by measuring the standard deviation of all pixels in images produced at a half-second cadence to produce a "variability image". Further details of the variability image are discussed in Morgan et al (2018) and Chhetri et al (2018) (hereafter, Papers I and II respectively). Following the convention established in Paper I, we term the continuum image (i.e.…”
Section: Datamentioning
confidence: 99%